Harnessing Mycoprotein: Unravelling Its Impact on Skeletal Muscle Health Through Systematic Review and Meta-Analysis - Dewi, Made Yudha Asrithari; Pangkahila, Evangelista Maria; Dananjaya, I Made Dwi (Bali Medical and Wellness Journal, 2024)
Background: Mycoprotein, a fungal-derived protein from Fusarium venenatum, has gained attention for its potential benefits in muscle health, particularly as an alternative to traditional animal-based proteins. Objectives: This systematic review and meta-analysis aimed to evaluate the effects of mycoprotein intake on skeletal muscle protein synthesis, plasma branched-chain amino acids (BCAAs), and post-prandial insulin response in healthy adults. Methods: The study followed the PRISMA guidelines and was registered in PROSPERO (CRD42024602558). A comprehensive search of the PubMed, Scopus, EuropePMC and Cochrane Library databases was conducted to identify randomized controlled trials comparing mycoprotein interventions with non-mycoprotein control groups. Trials were included if they reported outcomes related to muscle protein synthesis, plasma amino acid levels, or post-prandial insulin response. Risk of bias was assessed using the Cochrane risk-of-bias tool. Meta-analyses were performed using an inverse-variance–weighted, random-effects model. Results: Four randomized controlled trials involving 82 participants were included. Mycoprotein intake significantly increased muscle protein synthesis rates, with a fractional synthetic rate (FSR) increase of +0.01% per hour (95% CI: 0.01% to 0.02%, P < 0.001) compared to control groups. There was no significant difference in plasma BCAA levels between mycoprotein and control groups (mean difference: 2.83 µmol/L, 95% CI: -84.93 to 90.58, P > 0.05). However, post-prandial insulin response was significantly higher in the mycoprotein group at 30 minutes post-ingestion (mean difference: 8.15 mU/L, 95% CI: 5.70 to 10.59, P < 0.001). Conclusions: Mycoprotein intake shows potential benefits for increasing muscle protein synthesis and enhancing post-prandial insulin response. However, the limited sample sizes and short durations of the included trials suggest the need for larger, long-term studies to confirm these findings.